2020
DOI: 10.1177/0192513x20921520
|View full text |Cite
|
Sign up to set email alerts
|

Being a Working Grandmother, Mother, and Daughter at the Same Time: A “Double Sandwich” in a Four-generation Family

Abstract: A four-generation family imposes a burden of roles upon the grandparents, who are sandwiched between the ascendant generation of great-grandparents and the descendant generations of adult children and grandchildren. This study focused on working grandmothers, examines how they maneuver between the needs of their children, grandchildren and their task-load, the women did not perceive their situation negatively. Rather, they maneuver between the various roles and express a general contentment with their lives. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…The pattern of emotional reactions to stress was in line with Manor (2021), who showed that the Sandwich Generation could feel helpless or hopeless when they perceived multigenerational care as a burdening duty with no definite time limit.…”
Section: Because I Distract From My Work On the Other Hand If My Chil...supporting
confidence: 73%
See 1 more Smart Citation
“…The pattern of emotional reactions to stress was in line with Manor (2021), who showed that the Sandwich Generation could feel helpless or hopeless when they perceived multigenerational care as a burdening duty with no definite time limit.…”
Section: Because I Distract From My Work On the Other Hand If My Chil...supporting
confidence: 73%
“…Several studies have demonstrated negative consequences on the physical and psychological health of multigenerational caregivers, particularly for women, who most frequently have the responsibility as primary caregivers. Most research on the effects of nurturing on care providers has focused on caring for older relatives, usually referring to the father or mother, or in-laws (Luna et al, 2021;Manor, 2021). The challenges involved in multigenerational parenting generally impact the Sandwich Generation working women, including personal time, career development, and financial stability.…”
Section: Introductionmentioning
confidence: 99%
“…Estimates show that 24% of caregivers provide support to more than one relative ( AARP and National Alliance for Caregiving, 2020 ). The literature on dual family caregivers of older adults focuses primarily on “sandwiched” caregivers who assist two or more generations simultaneously ( Boyczuk & Fletcher, 2016 ; Manor, 2021 ), with a plethora of literature focusing on grandparents supporting adult children and raising grandchildren ( Hayslip et al, 2019 ). Many sandwiched caregivers not only have the responsibility of providing care for two generations, but also need to manage the added complexity of working full-time to support their family financially, which can contribute additional stress in their lives ( Hammer & Neal, 2008 ; Manor, 2021 ).…”
Section: Dual Caregivers Of Persons With Dementia: the Added Stress O...mentioning
confidence: 99%
“…Some researchers investigating grandparents raising grandchildren take the “sandwiched” caregiver focus a step further by analyzing the impact of being a “double sandwiched” caregiver who provides care not only to the generations directly above and below them but also to the generation two steps above them ( Meyer, 2014 ). A recent study of working women, mostly in their sixties, found that juggling the demands of multigenerational caregiving had negative physical, psychological, and social impacts on the women’s daily lives ( Manor, 2021 ). Other researchers have studied “compound” caregivers who serve in a dual role of caring for a child with an intellectual disability as well as for spouses, parents, other children or relatives, and friends.…”
Section: Dual Caregivers Of Persons With Dementia: the Added Stress O...mentioning
confidence: 99%
“…Building on models of the Sandwich Generation (Manor, 2021), that group of adults who are simultaneously helping their aging parents and their own children, family caregiving research has expanded in the past several decades. As a newer group of family caregivers enter the public awareness, there is much to be learned about grandchildren who are caregivers to their aging grandparents.…”
mentioning
confidence: 99%